Indonesian Modern Architectural Styles During The Late Colonial Period - Ashadi, Ashadi (Departement of Architecture, Universitas Islam Indonesia, 2026)
During the late period of colonialism in Indonesia, many buildings with various styles emerged in major cities, especially Jakarta, Bandung, Cirebon, Semarang, Solo, and Surabaya, in which the government and Dutch architects played an important role. This study aims to explore the architectural styles of modern Indonesian buildings in the late colonial period. The method used is comparative descriptive through literature study and field observation. The descriptive method was carried out on buildings by Dutch architects which were considered prominent. The analysis was carried out by comparing several buildings based on modern Western architectural references. The results of this study show that there were many modern buildings with various styles, which can be grouped into 5 styles: Neo-Classical, Neo-Renaissance, Art Deco, Vernacular, and Modern Tropical. These styles are the result of a tug-of-war between modern Western and Indonesian traditional architectural styles.